SILENCED BY TRADITION, RESURRECTED BY RESISTANCE: PROJECTION OF SUBALTERN WOMAN IN BANU MUSHTAQ’S STORY HEART LAMP - Sattar, Abdus (ShodhGyan-NU: Journal of Literature and Culture Studies, 2025)
This paper explores the silencing and subjugation of women within Indian patriarchal society through the lens of feminist criticism, with particular emphasis on Gayatri Chakravorty Spivak’s concept of the subaltern as articulated in her seminal essay Can the Subaltern Speak?. The discussion centres on Banu Mushtaq’s poignant narrative Heart Lamp, which vividly portrays the lived reality of Mehrun, a woman rendered voiceless and invisible within the confines of tradition, marriage, and cultural expectation. Through a close reading of the text, the paper examines how patriarchal structures perpetuate psychological and emotional violence, stripping women of agency and identity. Drawing upon Simone de Beauvoir’s feminist philosophy and integrating literary and cultural references, the paper situates female silence as a powerful metaphor for systemic oppression. At the same time, it highlights the moments of subtle resistance and self-assertion, suggesting that literature becomes a critical space where the subaltern woman, once marginalized, re-emerges as a symbol of endurance, protest, and transformation.